Insolvency Resolution Plans: Right of Erstwhile Management, Corporate Debtor. Issue 1 (June 2019) - George, Jasper Vikas
As the law under the Insolvency and Bankruptcy Code, 2016 progresses, many anomalies have surfaced which revolve around the resolution plans, which are meant for the survival of the corporate debtor. The National Company Law Appellate Tribunal recently held that it is permissible in law to give the opportunity to 'resolution applicants' for revising their offer before final approval. 1 Resolution plans play a key role in the corporate insolvency resolution process; therefore, the objectives of the author in the present article is, first, to analyse the importance of resolution plans, second, to examine the law regarding resolution plans in the Insolvency Code and, in the end, to analyse whether there is any necessity to maintain secrecy in reference to 'resolution plans' or whether giving a copy of the resolution plans to the corporate debtor will actually help the corporate debtor in getting necessary information for the health of their business for its benefit.